KAWASAN AGROWISATA DI KABUPATEN KAYONG UTARA DENGAN PENDEKATAN ARSITEKTUR BIOKLIMATIK - Nisma Wati; Jawas Dwijo Putro; Muhammad Ridha Alhamdani (JMARS: Jurnal Mosaik Arsitektur, 2022)
The development of tourism areas is one of the high priority sectors in Indonesia. One of the tourism sectors that has the potential to be developed in Indonesia is agrotourism. Sukadana is one of the sub-districts as well as the capital of North Kayong Regency which has many tourist destinations in the form of beaches, mountains and other natural beauty such as paoh hills, mangrove forests, etc. In addition to the tourism sector, Sukadana is also very famous for its durian products. Durian is one of the many varieties of fruits found in Sukadana District. However, in recent years there has been a decline in durian fruit sales. This is due to the pandemic period which sometimes limits the access of people outside the Sukadana District to visit. With this problem, the idea was created to create an agro-tourism area in North Kayong Regency that can support the distribution of fruits both during the pandemic and during normal times. The design of this agro-tourism area uses a bioclimatic architectural approach that pays attention to the relationship between architectural forms and their environment, especially in matters relating to the climate of the area. This agro-tourism area applies the concept of a Tourism and Education Village (Tourism And Education Village) where in addition to traveling, visitors can also get education related to agriculture and plantations. With the existence of this agro-tourism area, it is expected to affect the rate of economic growth in North Kayong Regency, especially the people of Sukadana District.